Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Given that:
$$z_3 = -\frac{1}{2}+j\frac{\sqrt{3}}{2}$$
evaluate the following:
$$(\overline{z}_3)^4 = [-\frac{1}{2}-j\frac{\sqrt{3}}{2}]^4$$ $$=[1\angle(-\frac{2\pi}{3})]^4$$ $$=1\angle(-\frac{8\pi}{3})$$ $$=1(\cos(-\frac{8\pi}{3})+j\sin(-\frac{8\pi}{3}))$$ $$=-\frac{1}{2}-j\frac{\sqrt{3}}{2}$$

To write $-\frac{1}{2}-j\frac{\sqrt{3}}{2}$ in polar form we first note that $|-\frac{1}{2}-j\frac{\sqrt{3}}{2}|=\sqrt{(\frac{1}{2})^2+(\frac{\sqrt{3}}{2})^2}=1$. With $a=-\frac{1}{2}$ and $b=-\frac{\sqrt{3}}{2}$, we obtain the reference angle of $\tan^-1(\frac{b}{a})=\tan^-1(\sqrt{3})=\frac{\pi}{3}$ radians. However $-\frac{1}{2}-j\frac{\sqrt{3}}{2}$ is in the third quadrant. Hence to get the argument of $-\frac{1}{2}-j\frac{\sqrt{3}}{2}$, we need to ratate $\frac{\pi}{3}$ (clockwise) by $\pi$ radians to get $\theta=\frac{\pi}{3}-\pi=-\frac{2\pi}{3}$.

My questions:
1. Why do we have to note that $|-\frac{1}{2}-j\frac{\sqrt{3}}{2}|=\sqrt{(\frac{1}{2})^2+(\frac{\sqrt{3}}{2})^2}=1$?
2. How do we know that $-\frac{1}{2}-j\frac{\sqrt{3}}{2}$ is in the third quadrant?

share|cite|improve this question
(1) If the modulus (absolute value) of $z$ is $r$, then $$z^n=(re^{i\theta})^n=r^ne^{in\theta}$$ allows us to compute the $n$th power of $z$ easily by first passing to polar form - but $r^n$ clearly depends on $r$ so it is necessary to compute it in order to do this method - rather than having to multiply numbers of the form $a+bi$ out $n$ times (or use the binomial theorem). (2) How do you know $(-1,-1)$ is in the third quadrant? Same reason: geometry (the quadrant depends only on the sign of the two components - or here, real and imaginary parts). – anon Jun 7 '12 at 6:36
up vote 1 down vote accepted

Given: $z = -\frac{1}{2}-\frac{\sqrt{3}}{2}i$

Find: $z^4$

In order to avoid multiplying (FOIL) numbers of the form $a+bi$ three times we make use de Moivre's of formula which is: $\left(\cos\theta+i\sin\theta\right)^n = \cos n\theta + i\sin n\theta$.

This means we need to transform the complex number $z$ into trig (polar) form: $r\left(\cos\theta+i\sin\theta\right)$.

As you noted, $r = \left|z\right| = 1$. In order to solve for $\theta$ we use the fact that $\tan\theta = \frac{\sqrt{3}/2}{1/2} = \sqrt{3}$. This means $\theta = \tan^{-1}\sqrt{3} = \frac{\pi}{3}$. However this is only the reference angle and not the full angle we need.

In order to find the quadrant where our complex number is located we can plot it using the x-axis for the real part and the y-axis for the complex part. So left $\frac{1}{2}$ and down $\frac{\sqrt{3}}{2}$. The point is in the third quadrant.

So the angle is $\theta = \pi+\frac{\pi}{3} = \frac{4\pi}{3}$.

Using de Moivre's formula:

$z = -\frac{1}{2}-\frac{\sqrt{3}}{2}i = 1\left(\cos\theta+i\sin\theta\right)\\ \Rightarrow z^4 = \left(1\left(\cos\theta+i\sin\theta\right)\right)^4\\ \Rightarrow z^4 = 1^4\left(\cos\theta+i\sin\theta\right)^4\\ \Rightarrow z^4 = 1^4\left(\cos 4\theta+i\sin 4\theta\right)\\ \Rightarrow z^4 = \cos 4\theta+i\sin 4\theta$

I included a couple more steps than needed in the last part to show how it all fits together.

share|cite|improve this answer
You don't need to FOIL $z$ three times, you just need to square it twice. – Stefan Smith Jun 10 '12 at 13:32

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.